Potenzialità dei nuovi sistemi indossabili per la scansione 3D - Una sperimentazione del Pegasus Backpack di LeicaGeosystems presso il Palazzo Ducale di Modena - Castagnetti, Cristina; Mancini, Francesco; Rivola, Riccardo; Rossi, Paolo; Oppici, Simone; Albano, Valentina; Formentini, Marco (Archeomatica, 2017)
The terrestrial laser scanning is a well established technology for a wide range of applications. Recently the development of wearable systems based on multiple profilers and cameras opens to new challenging field of applications. The potentialities of such systems in terms of accuracy, productivity, completeness of the final dataset has been tested and described in the paper. The case study is provided by the Military Academy of Modena where an expeditious survey was carried out both in internal and external environments with the objective of evaluating the performance of the Leica Pegasus Backpack, a wearable system, in comparison with the Leica ScanStation C10, a traditional terrestrial laser scanner in static position. The field test allows to highlight the most suitable applications for these wearable systems.